Prawo człowieka do śmierci przegląd orzecznictwa Europejskiego Trybunału Praw Człowieka - Kalita, Tomasz (Przegląd Prawno-Ekonomiczny, 2012)
Streszczenie dostępne wyłącznie w jezyku angielskim: The article focuses on the problem of the right to die on the ECHR’s jurisdiction. The right to die is treated as the ethical or institutional entitlement of the individual to commit suicide or to undergo voluntary euthanasia. Possession of this right is often understood to mean that a person with a terminal illness should be allowed to commit suicide or assisted suicide or to decline life-prolonging treatment, where a disease would otherwise prolong their suffering to an identical result. The question of who, if anyone, should be empowered to make these decisions is often central to debate.